2020
DOI: 10.1111/avsc.12499
|View full text |Cite
|
Sign up to set email alerts
|

Response of grassland vegetation composition to different fertilizer treatments recorded over ten years following 64 years of fertilizer applications in the Rengen Grassland Experiment

Abstract: QuestionsFertilizer application is a key driver affecting the diversity and conservation value grassland vegetation. Using a long‐term fertilization experiment in mountain grassland, we addressed the following questions: (a) what is the effect of long‐term fertilizer applications on species richness and plant species composition, and (b) is there any detectable trend in plant species composition during ten years of continuous observation?LocationThe Rengen Grassland Experiment, Eifel Mountains, Germany (establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…For instance, Festuca rubra (one of the dominant grass species in our experimental site), which has many ecotypes (Grime et al, 1988) in comparison with other common grass species, is well adapted to various abiotic conditions including drought. Its variability in time can be explained by compensatory dynamic (Lepš et al, 2018) in which cover of species like Festuca rubra can increase even under dry conditions (Titěra et al, 2020) while compensating for the possible decline in cover of other species like Poa trivialis, which is less tolerant to drought (Peeters et al, 2004). Gaisler et al (2018) also reported similar results from a long‐term experiment (13 years) in which different functional groups such as tall graminoids and tall forbs fluctuated without any clear stable trend for any particular treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Festuca rubra (one of the dominant grass species in our experimental site), which has many ecotypes (Grime et al, 1988) in comparison with other common grass species, is well adapted to various abiotic conditions including drought. Its variability in time can be explained by compensatory dynamic (Lepš et al, 2018) in which cover of species like Festuca rubra can increase even under dry conditions (Titěra et al, 2020) while compensating for the possible decline in cover of other species like Poa trivialis, which is less tolerant to drought (Peeters et al, 2004). Gaisler et al (2018) also reported similar results from a long‐term experiment (13 years) in which different functional groups such as tall graminoids and tall forbs fluctuated without any clear stable trend for any particular treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These disparities between different studies may be explained by differences in experimental sites’ environments such as nutrient supply, water or light/shade conditions (Milchunas & Lauenroth, 1993; Borer et al, 2014). Especially leguminous species are generally known for their positive response to P and K and negative response to the high inputs of N, NP or NPK (e.g., Čop & Eler, 2019; Titěra et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The second article we want to mention (Titěra et al ., 2020) focused on one of the oldest continuously running ecological experiments on the European mainland: the Rengen Grassland Experiment in western Germany, established in 1941 (Hejcman et al ., 2007). For 10 years (2005–2014), the authors recorded plant species composition and covers of individual species in permanent plots with different fertilizer application treatments.…”
Section: Editors’ Award For 2020mentioning
confidence: 99%
“…If long‐term experiments like the Park Grass (see above) or the Rengen Grassland Experiment (Hejcman et al ., 2007; Titěra et al ., 2020) are rare, even rarer is the possibility to compare the consistency of results, using comparable set‐ups, across different regions of the world. Ward et al .…”
Section: Permanent Plots As a Tool For Vegetation Sciencementioning
confidence: 99%